The effect of the structured introduction as a cognitive strategy in the collection and retention of musical information among the students of the Art Education Branch - Teachers Colleg (Journal of the College of Basic Education, 2022)
It is an accepted fact that the goal of teaching is to achieve the desirable behavior of the learnerAnd his tool in that is various factors and variables, on top of which stands the teacher and his strategy in achieving changeIn that behavior through great effort to increase the learner's mental ability to store informationAnd retrieve and benefit from it whenever needed